If you made a million - Schwartz, David M.; Kellogg, Steven (New York : Lothrop, Lee & Shepard Books, 1989)
Describes the various forms which money can take, including coins, paper money, and personal checks, and how it can be used to make purchases, pay off loans, or build interest in the bank.
Keywords: Finance, Personal -- Juvenile literature; Finance, Personal; Money